The Effect of Solvent Types on The Antibacterial and Cytotoxic Activity of Lino Bark Extract - Landi Pote, Lodowik; Taek, Maximus M.; Nadut, Anggelinus; Latumakulita, Gertreda (Universitas Nusa Bangsa, 2025)
The G. koordersiana Burret plant, especially its bark, is used by the Sumba community to treat wounds, ulcers, and liver. This study aims to determine the effect of solvent types on the antibacterial and cytotoxic activity of G. koordersiana Burret extract. The research methods used were maceration method, antibacterial test, and cytotoxic test of G. koordersiana Burret bark extract. The results showed that the yield of ethanol, methanol, and n-hexane extracts were 42.15%; 41.65%; and 0.62%, respectively. Ethanol and methanol extracts had antibacterial activity against E. coli and S. aureus bacteria, while n-hexane extract did not show antibacterial activity against both bacteria. Cytotoxic tests showed that the LC50 values ​​of ethanol, methanol, and n-hexane extracts were 61.35 ppm; 758.58 ppm; and 2,494,181.19 ppm, respectively. Ethanol and methanol extracts had antibacterial activity and were toxic, while n-hexane extract did not show antibacterial activity and was not toxic. The antibacterial and cytotoxic activities of ethanol and methanol extracts showed the presence of secondary metabolite compounds of the alkaloid, phenolic, flavonoid, tannin, triterpenoid, and saponin groups, while n-hexane extract contained triterpenoid compounds that had no inhibitory power against bacteria or cytotoxic activity.